KONFLIK BATIN TOKOH DALAM CERPEN “KEBAHAGIAAN YANG MEMBUNUH” KARYA ATTA VERIN: KAJIAN PSIKOANALISIS SIGMUND - Nagita Ayu Windorika; Eni Nurhayati; Mohammad Rokib; Alya Ragil Ramadhani; Isti Choirunnisa Zalsabila; Silviana Putri Ema Susanti (STKIP Subang, 2026)
This study examines the inner conflict and personality dynamics of the main character in Atta Verin's short story